Osteology Supports a Stem-Galliform Affinity for the Giant Extinct Flightless Bird Sylviornis neocaledoniae (Sylviornithidae, Galloanseres). - Trevor H Worthy (PLoS ONE, 2016)
The giant flightless bird Sylviornis neocaledoniae (Aves: Sylviornithidae) existed on La Grande Terre and Ile des Pins, New Caledonia, until the late Holocene when it went extinct shortly after human arrival on these islands. The species was generally considered to be a megapode (Megapodiidae) until the family Sylviornithidae was erected for it in 2005 to reflect multiple cranial autapomorphies. However, despite thousands of bones having been reported for this unique and enigmatic taxon, the postcranial anatomy has remained largely unknown. We rectify this deficiency and describe the postcranial skeleton of S. neocaledoniae based on ~600 fossils and use data from this and its cranial anatomy to make a comprehensive assessment of its phylogenetic affinities. Sylviornis neocaledoniae is found to be a stem galliform, distant from megapodiids, and the sister taxon to the extinct flightless Megavitiornis altirostris from Fiji, which we transfer to the family Sylviornithidae. These two species form the sister group to extant crown-group galliforms. Several other fossil galloanseres also included in the phylogenetic analysis reveal novel hypotheses of their relationships as follows: Dromornis planei (Dromornithidae) is recovered as a stem galliform rather than a stem anseriform; Presbyornis pervetus (Presbyornithidae) is the sister group to Anseranatidae, not to Anatidae; Vegavis iaai is a crown anseriform but remains unresolved relative to Presbyornis pervetus, Anseranatidae and Anatidae. Sylviornis neocaledoniae was reconstructed herein to be 0.8 m tall in a resting stance and weigh 27-34 kg. The postcranial anatomy of S. neocaledoniae shows no indication of the specialised adaptation to digging seen in megapodiids, with for example, its ungual morphology differing little from that of chicken Gallus gallus. These observations and its phylogenetic placement as stem galliforms makes it improbable that this species employed ectothermic incubation or was a mound-builder. Sylviornis neocaledoniae can therefore be excluded as the constructor of tumuli in New Caledonia.